WORK MOTIVATION IMPROVEMENT THROUGH TRAINING AND EDUCATION DEVELOPMENT - Nardi Nardi; Nita Rislawati; Sofia Ulfa Eka Hadiyanti; Bun Yamin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research was conducted at PT. Harmoni Mitra Utama in Samarinda City and aims to determine the effect of training and educational development on employee work motivation using SPSS 22.0. The population in this study were all employees of PT. Harmoni Mitra Utama Samarinda and the sample is a total population of 50 employees. This type of research is an explanatory research with the quantitative approach. The research method used is a form of explanatory survey method and conducted to answer the hypothesis that there is the influence of training and educational development on the work motivation of employees of PT. Harmoni Samarinda's main partner. The results of this study indicate that training has no significant effect on the work motivation of employees of PT. Harmoni Mitra Utama Samarinda, while the development of education has a significant influence on the work motivation of employees of PT. Harmoni Mitra Utama Samarinda. Education is an effort to prepare employees through educational activities. Training is a short-term educational process that is organized in learning knowledge and skills for certain goals.